GIANT CENTROSPHERES IN DEGENERATING MESENCHYME CELLS OF TISSUE CULTURES - Lewis, Warren H. (The Rockefeller University Press, 1920)
1. Degenerating mesenchyme cells in tissue cultures cultivated in various modifications of Locke's solution often have giant centrospheres. 2. These giant centrospheres develop gradually around the centriole and in their most complete condition consist of centriole, medullary zone, and cortical zone. 3. Preceding the appearance of the centrosphere the centriole is surrounded by degeneration granules or granules and vacuoles, and as the centrosphere develops these are forced first to the periphery of the medullary zone and latter, when it develops, to the periphery of the cortical zone. 4. The mitochondria become orientated about the centriole and centrosphere, at first more or less radially, later concentrically. They change from threads to rods and granules. 5. The giant centrospheres and cancer cell inclusions (Plimmer's bodies, etc.) are identical.